2017
DOI: 10.1021/acs.jmedchem.7b01072
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Basis for Allosteric Inhibition of Acid-Sensing Ion Channel 1a by Ibuprofen

Abstract: A growing body of evidence links certain aspects of nonsteroidal anti-inflammatory drug (NSAID) pharmacology with acid-sensing ion channels (ASICs), a small family of excitatory neurotransmitter receptors implicated in pain and neuroinflammation. The molecular basis of NSAID inhibition of ASICs has remained unknown, hindering the exploration of this line of therapy. Here, we characterized the mechanism of inhibition, explored the molecular determinants of sensitivity, and sought to establish informative struct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
25
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(26 citation statements)
references
References 55 publications
0
25
0
1
Order By: Relevance
“…Placement of a Cl - ion at this high pH binding site off of Lys 77 and Lys 422 partially occludes the narrow extracellular fenestrations that provide access for Na + ions to the channel pore ( Fig 5D and 5E ) and that undergo a dramatic expansion upon channel activation[ 23 ]. Furthermore, a recent study demonstrated that Lys 422, positioned less than 3 Å from the high pH Cl - site, is important for inhibition of ASIC1a by ibuprofen[ 35 ], indicating that this region of the channel is critical for proton-dependent gating and serves as a binding site for channel modulators. Moreover, while the biological significance of a high pH Cl - site on the resting channel remains unknown, the absence of a bound Cl - at the canonical low pH site in crystal structures of the resting channel at high pH demonstrates how Cl - ions, in addition to protons and divalent cations, play an important role in the pH-dependent function of ASICs.…”
Section: Resultsmentioning
confidence: 99%
“…Placement of a Cl - ion at this high pH binding site off of Lys 77 and Lys 422 partially occludes the narrow extracellular fenestrations that provide access for Na + ions to the channel pore ( Fig 5D and 5E ) and that undergo a dramatic expansion upon channel activation[ 23 ]. Furthermore, a recent study demonstrated that Lys 422, positioned less than 3 Å from the high pH Cl - site, is important for inhibition of ASIC1a by ibuprofen[ 35 ], indicating that this region of the channel is critical for proton-dependent gating and serves as a binding site for channel modulators. Moreover, while the biological significance of a high pH Cl - site on the resting channel remains unknown, the absence of a bound Cl - at the canonical low pH site in crystal structures of the resting channel at high pH demonstrates how Cl - ions, in addition to protons and divalent cations, play an important role in the pH-dependent function of ASICs.…”
Section: Resultsmentioning
confidence: 99%
“…Placement of a Cl − ion at this high pH binding site off of Lys 77 and Lys 422 partially occludes the narrow extracellular fenestrations that provide access for Na+ ions to the channel pore (Figure 5D-E) and that undergo a dramatic expansion upon channel activation(23). Furthermore, a recent study demonstrated that Lys 422, positioned less than 3 Å from the high pH Cl − site, is important for inhibition of ASIC1a by ibuprofen(35), indicating that this region of the channel is critical for proton-dependent gating and serves as a binding site for channel modulators. Moreover, while the biological significance of a high pH Cl − site on the resting channel remains unknown, the absence of a bound Cl − at the canonical low pH site in crystal structures of the resting channel at high pH demonstrates how Cl − ions, in addition to protons and divalent cations, play an important role in the pH-dependent function of ASICs.…”
Section: Resultsmentioning
confidence: 99%
“…Ibuprofen and flurbiprofen, for example, inhibit ASIC1a containing channels with an IC50 value of 350 µM. The proposed mechanism of action of the nonsteroidal anti-inflammatory drugs is that of allosteric inhibition of the channels by slowing the recovery after inactivation (Dorofeeva, Barygin, Staruschenko, Bolshakov, & Magazanik, 2008;Lynagh, Romero-Rojo, Lund, & Pless, 2017). Other drugs like Aspirin and salicylate inhibit ASIC3 containing channels (Voilley, 2004).…”
Section: Exogenous Ligandsmentioning
confidence: 99%